The influence of external sector on ecuadorian liquidity, 2000-2016 - Espinoza Estrella, Bryan (2020)
The purpose of this paper is to study the influence of the representative variables of the external sector within the Ecuadorian liquidity, for the period dollarized between the years 2000 to 2016, specifically focusing on the variables European and American international interest rate, exchange rate, assets and exportations. In addition, this paper analyzed the impact of liquidity on the gross domestic product. As can be seen from the results obtained, the country is more vulnerable to different external shocks, mainly, it is more sensitive to the foreign interest rate. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/919